PELAKSANAAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN TES HASIL BELAJAR BERBASIS KETERAMPILAN BERPIKIR KRITIS - Sungep Sungep (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This study refers to the teacher's competence in compiling tests of learning outcomes that are still low and seems to be a condition for the availability of the test only, even though the test is used as a benchmark for students' abilities after experiencing the learning process. For this reason, this study aims to guide teachers in developing learning outcomes tests, especially those based on critical thinking skills. This research is a classroom action research conducted on 24 teachers of 006 Pontian Mekar Elementary School. The research will be carried out from July to August 2019. Data analysis uses observation sheets. The results showed an increase in teacher competency in preparing critical thinking skills learning outcomes test with a percentage in the construction aspect I of 72% with a quite appropriate category to 85% which is included in the appropriate category, in the material aspect in the cycle I gained a percentage of 75% which is a category quite appropriate increased to reach 87% which is classified in the category of very appropriate, and for aspects of language also increased from 68% in the first cycle increased to 82% in the second cycle. The conclusion of this study is that the implementation of academic supervision can improve teacher competence in compiling tests of learning outcomes based on critical thinking skills